Incomplete Partition : The Genesis of the Kashmir Dispute 1947-1948 - Lamb, Alastair (Karachi Oxford University Press, 2002)
Fifty years on, the Kashmir dispute between India and Pakistan seems to be no nearer solution than it was in 1947 when the British Indian Empire ended with the partition of the Indian subcontinent. Alastair Lamb argues, on the basis of research into a great deal of archival and other documentary material, that in many ways the Kashmir question was a direct product of the process of partition which in important respects was never completed; and any serious attempt at its resolution will inevitably involve a conscious effort to complete that process. This book adds a detailed study of the treatment of the Kashmir issue by the United Nations during the course of the year 19348. A concluding chapter considers the events of 1947 and 1948 in the light of the current situation and explores the possibilities for some kind of settlement of the dispute which has so profoundly disrupted relations between India and Pakistan for virtually the whole of their lives as sovereign states.
Include Maps and Index.
Keywords: India--Jammu and Kashmir -- Pakistan -- India -- Diplomatic relations -- Politics and government